2018
DOI: 10.1208/s12249-018-1093-1
|View full text |Cite
|
Sign up to set email alerts
|

Getting the Jump on the Development of Bullfrog Oil Microemulsions: a Nanocarrier for Amphotericin B Intended for Antifungal Treatment

Abstract: Amphotericin B (AmB), a potent antifungal drug, presents physicochemical characteristics that impair the development of suitable dosage forms. In order to overcome the AmB insolubility, several lipid carriers such as microemulsions have been developed. In this context, the bullfrog oil stands out as an eligible oily phase component, since its cholesterol composition may favor the AmB incorporation. Thus, the aim of this study was to develop a microemulsion based on bullfrog oil containing AmB. Moreover, its th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…The results showed that both BFO and BFO-CV were not able to decrease the cell viability at all tested times and concentrations, suggesting an absence of toxicity of these products against macrophages Raw 264.7 . These data are in accordance to previous literature reports regarding the cytotoxicity evaluation of BFO against an epithelial cell lineage 3T3 and a macrophage cell lineage Raw 264.7 6,29 . These reports revealed that both BFO and its emulsified system, at concentrations up to 100 µg.mL 1 , did not show cytotoxicity up to 72 hours of treatment against these cell lineages.…”
Section: In Vitro Cytotoxicity Evaluationsupporting
confidence: 93%
“…The results showed that both BFO and BFO-CV were not able to decrease the cell viability at all tested times and concentrations, suggesting an absence of toxicity of these products against macrophages Raw 264.7 . These data are in accordance to previous literature reports regarding the cytotoxicity evaluation of BFO against an epithelial cell lineage 3T3 and a macrophage cell lineage Raw 264.7 6,29 . These reports revealed that both BFO and its emulsified system, at concentrations up to 100 µg.mL 1 , did not show cytotoxicity up to 72 hours of treatment against these cell lineages.…”
Section: In Vitro Cytotoxicity Evaluationsupporting
confidence: 93%
“…The fungal MIC was performed using the biological strains aforementioned (Section 2.1.2). The inocula were diluted in Mueller–Hinton broth (MHB) at the ratio of 1:30 according to an adaptation from the method described by Oliveira et al (2018) [18]. The BBE and the BME were diluted in sterile MHB and bullfrog oil was diluted with DMSO at 1% in sterile MHB in order to obtain an oil concentration of 4 mg·mL −1 for all samples.…”
Section: Methodsmentioning
confidence: 99%
“…Turk’s solution at 1% and saline solution at 0.9% were used as positive and negative control, respectively. Finally, the hemolytic potential was calculated according to the Equation (1) [18]:Hp(%)=100×AsAnAp where, Hp = Hemolytic potential (in percentage); As = Absorbance of tested sample; An = Absorbance of the Negative Control; Ap = Absorbance of the Positive Control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of Oliveira et al. have shown that bullfrog oil obtained from adipose tissues of amphibious wood frogs could significantly enhance antifungal activities of AMB and reduce its toxicity ( Oliveira et al., 2018 ). Ludwig et al.…”
Section: Introductionmentioning
confidence: 99%